Caregiver burden, and parents' perception of disease severity determine health-related quality of life in paediatric patients with intoxication-type inborn errors of metabolism - Florin Bösch; Markus A. Landolt; Matthias R. Baumgartner; Susana Fernandez; Patrick Forny; Matthias Gautschi; Sarah C. Grünert; Johannes Häberle; Carolina Horvath; Daniela Karall; Danila Lampis; Marianne Rohrbach; et al. (Molecular Genetics and Metabolism Reports, 2022)
Background: Living with a non-acute (phenylketonuria) or acute (e.g. urea cycle disorders, organic acidurias) intoxication-type inborn error of metabolism (IT-IEM) can have a substantial impact on health-related quality of life (HrQoL) of paediatric patients and their families. Parents take primary responsibility for treatment monitoring and experience worry and fear about their child's health status. Quantitative evidence on parental psychological factors which may influence the HrQoL of patients with IT-IEM are sparse to non-existent. Methods: In this multicenter survey study 50 parents of IT-IEM patients (ages 5–19) assessed the severity of their child's disease, reported on caregiver burden, and proxy-rated their child's HrQoL. Additionally, 35 patient self-reports on HrQoL were obtained (n = 16 female patients, n = 19 male patients). Multiple linear regressions were conducted to examine the predictive power of child age, sex, medical diagnosis type (acute / non-acute), parental perceived disease severity and caregiver burden on patients' HrQoL. Mediation analyses were used to investigate the relation of caregiver burden and parental ratings of disease severity with patients' HrQoL. Results: Significant regression models for self-reported [F(5,34) = 10.752, p < .001, R2 adj.. = 0.59] and parent proxy reported HrQoL [F(5,49) = 20.513, p < .001, R2 adj.. = 0.67] emerged. High caregiver burden and perceived disease severity predicted significantly lower patient self- and proxy-reported HrQoL while type of diagnosis (acute versus non-acute) did not. Female sex predicted significantly lower self-reported HrQoL. High caregiver burden was the mediating factor between high perceived severity of the child's disease and lower proxy- by parent rated HrQoL. Conclusion: Detecting elevated burden of care and providing support for parents seems crucial to prevent adverse consequences for their children's HrQoL. Intervention studies are needed, to assess which support programs are most efficient.